Human rights, human security, and state security : the intersection - Takahashi, Saul (Praeger, an imprint of ABC-CLIO, LLC, 2014)
This book provides innovative thinking from a variety of perspectives on the important human rights, human security, and national security policy issues of today-and how these issues intersect.